Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/kin.20533
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent kinetics for the ozonolysis of selected chlorinated alkenes in the gas phase

Abstract: The ozonolysis of olefinic species is an important tropospheric process impacting on climate and human health. However, few studies have investigated these reactions as a function of temperature and even less information is available upon the effects of alkene heteroatomic substitution on the Arrhenius parameters. The electron-withdrawing capacity of substituents about the olefinic bond strongly influences the rate of alkene ozonolysis. To understand better the effect of these substitutions, the temperature-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Zhang et al 37 reported k 34 = (1.80 ± 0.29) × 10 −19 cm 3 molecule −1 s −1 . Within the error bars, the present work agrees with the reported values by Leather et al 35 with regard to k 33 , but not k 34 . Both the reported values for k 33 and k 34 by Blume et al 36 and the value for k 34 by Zhang et al 37 are all outside the error limits of the present study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Zhang et al 37 reported k 34 = (1.80 ± 0.29) × 10 −19 cm 3 molecule −1 s −1 . Within the error bars, the present work agrees with the reported values by Leather et al 35 with regard to k 33 , but not k 34 . Both the reported values for k 33 and k 34 by Blume et al 36 and the value for k 34 by Zhang et al 37 are all outside the error limits of the present study.…”
Section: Resultssupporting
confidence: 93%
“…Two reports exist in the literature on k 33 and three on k 34 , some of which do not agree with each other, see Table 4. Leather et al 35 reported k 33 = (4.9 +4.0 −2.2 ) × 10 −21 , and k 34 = (8 +10 −5.4 ) × 10 −19 cm 3 molecule −1 s −1 , while Blume et al 36 reported k 33 = 3.59 × 10 −20 and k 34 = 2.46 × 10 −19 cm 3 molecule −1 s −1 . Zhang et al 37 reported k 34 = (1.80 ± 0.29) × 10 −19 cm 3 molecule −1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…222 The E a and pre-exponential factor A for the temperature dependence of reactions of O 3 with cis-1,2-dichloroethene, trans-1,2-dichloroethene, trichloroethene, tetrachloroethene, 2-chloropropene, and 3-chloro-1-butene have been reported. 223 The Arrhenius expressions for the gas-phase reactions of 1-butene, isobutene, 2-methyl-1-butene, and 3-methyl-1-butene with O 3 were determined, and the reaction rate constant and activation energy agreed with those reported in the literature. 224 The Arrhenius expressions, rate constants, and atmospheric residence times for gas-phase reactions of α- (71) and β-farnesene (72), β-myrcene (73), and β-ocimene (74) with O 3 and • OH radicals using He as the diluent gas were reported.…”
Section: Ozonolysis and Ozonationsupporting
confidence: 62%
“…22 These rate coefficients were also determined using the absolute method, where ozone was monitored using a Monitor Labs Inc. 8810 ozone analyzer. The resulting Arrhenius expressions are published elsewhere, 23 extrapolations of which provide experimental estimates of the room temperature rate coefficients presented in this work.…”
Section: Experimental Methodologymentioning
confidence: 99%